TREATMENT OF LAMINITIS IN SPORT HORSES AND PREVENTION - Djabbarova Dilnoza Khasilbekovna; Komilov Hajibay; Karimov Kadirali (Journal of new century innovations, 2023)
Annotation. Hoof diseases in horses occur for a number of reasons. Laminitis is one of the diseases of the hoof, and it is a non-infectious internal disease that can be treated as a result of a number of mistakes and deficiencies in the feeding, keeping, training and use of animals, as well as poisoning. cases of laminitis are observed.